1996
DOI: 10.7146/brics.v3i11.19974
|View full text |Cite
|
Sign up to set email alerts
|

Near-Optimal, Distributed Edge Colouring via the Nibble Method

Abstract: We give a distributed randomized algorithm to edge colour a network. Let G be a graph with n nodes and maximum degree ∆. Here we prove:• If ∆ = Ω(log 1+δ n) for some δ > 0 and λ > 0 is fixed, the algorithm almost always colours G with (1 + λ)∆ colours in time O(log n).• If s > 0 is fixed, there exists a positive constant k such that if ∆ = Ω(log k n), the algorithm almost always colours G with ∆ + ∆/ log s n = (1 + o(1))∆ colours in time O(log n + log s n log log n).By "almost always" we mean that the algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 19 publications
0
54
0
Order By: Relevance
“…al. [11] used the Rődl nibble method to improve this to a randomized (1 + ϵ)∆-edge-coloring in time O(log n), as long as ∆ = ω(log n). Grable and Panconesi [14] showed that if for every edge e = (u, w), the degree of either u or w is sufficiently large (at least 2 Ω( log n log log n ) ), then a (1 + ϵ)∆-edge-coloring, for an arbitrarily small constant ϵ > 0, can be computed in O(log log n) time by a randomized algorithm.…”
mentioning
confidence: 99%
“…al. [11] used the Rődl nibble method to improve this to a randomized (1 + ϵ)∆-edge-coloring in time O(log n), as long as ∆ = ω(log n). Grable and Panconesi [14] showed that if for every edge e = (u, w), the degree of either u or w is sufficiently large (at least 2 Ω( log n log log n ) ), then a (1 + ϵ)∆-edge-coloring, for an arbitrarily small constant ϵ > 0, can be computed in O(log log n) time by a randomized algorithm.…”
mentioning
confidence: 99%
“…We shall lay down conditions on f and on algorithms computing f locally that will enable the methods in the previous section to be extended to to derive a sharp concentration result on f . In particular, we indicate how the edge colouring algorithm above [8] as well as the edge and vertex colouring algorithms from [2,3] follow directly as well as the analysis of a vertex colouring process in [7]. Suppose that f is a function determined by each vertex v of the graph assigning labels (v) to itself and labels (v, e), e ∈ N(v) to its incident edges by some randomised process.…”
Section: A General Frameworkmentioning
confidence: 99%
“…So, a partition of the edges into a small number of colour classes -i.e. a "good" edge colouring-gives an efficient schedule to perform data transfers (for more details, see [8,2]). The analysis of edge colouring algorithms published in the literature is extremely long and difficult and that in [8] is moreover, based an a certain ad hoc extension of the Chernoff-Hoeffding bounds.…”
Section: Introductionmentioning
confidence: 99%
“…Panconesi and Srinivasan [PS97] give the first such result. Dubhashi, Grable and Panconesi [DGP98] later improve this to (1 + ε)∆-edge-coloring in O(log n) rounds, when ∆ = Ω(log 1+Ω(1) n). This was later refined and extended to graphs of degree ∆ ≥ C 0 , for a constant C 0 depending on ε.…”
Section: Degree Splitting and Edge Orientationsmentioning
confidence: 99%